An Analysis of Seating Arrangement on Students’ Learning Attention - Ahmad Syaifullah; Munir Munir; Amra Ariyani (Journal of Excellence in English Language Education, 2022)
The objective of this research was to find out how row and U-shaped seating arrangements affect the students’ learning attention. This research employed a descriptive qualitative method. The subject of this research was class VIII A consisted of 25 students taken by using purposive sampling. The instruments in collecting data were observation checklist and interview. The data were obtained through observation to see the Row and U-shaped seating arrangements and kinds of students’ learning attention. The data from the interview were analyzed by recording and transcribing them. The result of this research showed that the U-Shaped seating arrangement is a better form to apply in the class than the Row form. The classroom needs a lot of communication and communication is exchanging information with each other. The information exchange happened by giving attention. Students learning engagement is formed by eye contact with the teacher or among the students themselves because eye contact stimulates external factors to get maximum attention. A u-shaped form is the best form to facilitate eye contact.